COVID-19 pandemic: A global health burden - Akande, Oluwatosin; Akande, Tanimola (The Nigerian postgraduate medical journal, 2020)
Coronavirus disease 2019 (COVID-19) pandemic began in China with a group of severe pneumonia cases, later identified to be caused by the severe acute respiratory syndrome coronavirus 2 in December 2019. Thailand reported the first COVID-19 case outside of China on 13th January 2020, Africa reported its first case in Egypt on 14th February 2020 and Nigeria reported its index case of COVID-19 on 27th February 2020. Virtually, all countries in the world are affected, with over 5 million cases reported globally. A literature search was conducted using publications from academic databases and websites of relevant organisations. The disease is associated with typical and atypical signs and symptoms, mimicking other common illnesses. Nigeria is now in the phase of widespread community transmission as almost all the states have reported confirmed cases. The pandemic has shown a wide range of case-fatality rate (CFR) globally; this is postulated to be related to the demographics, existing health systems and probably other unidentified factors. There has been a steady increase in the burden caused by the disease in Nigeria with a relatively stable CFR, which is lower than the global CFR. Health systems have responded with the guidelines for prevention, management, and surveillance of the disease, while effort is being put in place to find a vaccine and a specific therapy for the cure of the disease. The pandemic has had a severe effect on health systems globally, including an unintended disruption in the service delivery of other diseases. It has the potential to disrupt the weak health system in Nigeria significantly. As such, a combination of non-pharmaceutical preventive measures that are cost-effective needs to be scaled up to prevent it from further weakening the existing health system.